Programa de créditos agrarios y desarrollo económico de sus beneficiarios en la provincia de Maynas 2021 - Tello Perez, Joan Ari (2022)
The general objective of the research presented was to determine the relationship between the agricultural credit program and the economic development of its beneficiaries in the province of Maynas, 2021, likewise, a descriptive study - correlational and non-experimental design has been chosen, from which It has taken a sample of 100 people being farmers, who were surveyed through a questionnaire. Therefore, the following results were obtained: the agricultural credit program is regular (26%) because sometimes the entity provides information on the requirements that must be presented to access the credit requested, as well as home verification sometimes It is carried out by an analyst, in addition, that the disbursement is sometimes made to the respective personal account granted by the entity, sometimes they follow up on the credits granted, on the other hand, they have almost never received personal visits from the first day of delinquency Likewise, economic development is qualified as regular (26%), since financing sometimes allows it to increase its agricultural production, also, the entity almost never has control tools to record its income and production expenses, likewise, they state that at Sometimes agricultural production increases the sources of employment for farmers and, finally, they mention that long-term credit has never allowed them to increase their economy. Finally, the research concludes that the agricultural credit program is related to economic development in a significant way with (rho=.754; sig.=0.000); in the same way it happens with the economic system (rho=.592; sig.=0.000); likewise, with productive structure (rho=.642; sig.=0.000); social factors (rho=.704; sig.=0.000); and growth (rho=.608; sig.=0.000).